2010
DOI: 10.1021/ja1023496
|View full text |Cite
|
Sign up to set email alerts
|

Using a One-Electron Shuttle for the Multielectron Reduction of CO2 to Methanol: Kinetic, Mechanistic, and Structural Insights

Abstract: Pyridinium and its substituted derivatives are effective and stable homogeneous electrocatalysts for the aqueous multiple-electron, multiple-proton reduction of carbon dioxide to products such as formic acid, formaldehyde, and methanol. Importantly, high faradaic yields for methanol have been observed in both electrochemical and photoelectrochemical systems at low reaction overpotentials. Herein, we report the detailed mechanism of pyridinium-catalyzed CO(2) reduction to methanol. At metal electrodes, formic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
356
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 521 publications
(382 citation statements)
references
References 49 publications
12
356
0
2
Order By: Relevance
“…Such organic-mediated reactivity with regards to the conversion of CO 2 to chemical fuels has been reviewed by Hu and coworkers [5]. The report describes the use of tetraalkylammonium salts [6], ionic liquids [7], and pyridinium derivatives [8] that have been shown to act as mediators in the selective (photo-) electrochemical reduction of CO 2 to products such as CO and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Such organic-mediated reactivity with regards to the conversion of CO 2 to chemical fuels has been reviewed by Hu and coworkers [5]. The report describes the use of tetraalkylammonium salts [6], ionic liquids [7], and pyridinium derivatives [8] that have been shown to act as mediators in the selective (photo-) electrochemical reduction of CO 2 to products such as CO and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…In this study56 they concluded that pyridinium is reduced on a Pt electrode, including a pyridinium‐bound proton to form a surface hydride which was further supported by the work of Batista 57. Indeed, the study from Bocarsly and co‐workers55 created more controversy in the field and drove several studies 58, 59, 60, 61. Another study was conducted by Savéant and co‐workers arguing the plausibility of this catalytic process 62.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 76%
“…They also clarified that formic acid and formaldehyde are the intermediate or side products formed during the electrochemical reduction of CO 2 to methanol. That reaction requires a proton‐assisted six‐electron reduction with a formal potential of −380 mV (vs. NHE) 55. According to their findings the mechanism involves multiple single‐electron transfers.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 98%
See 2 more Smart Citations